Structural Brain Network Reorganization in Patients with Neuropsychiatric Systemic Lupus Erythematosus - Xu, X.; Hui, E.S.; Mok, M.Y.; Jian, J.; Lau, C.S.; Mak, H.K.F. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Patients with neuropsychiatric systemic lupus erythematosus have worse outcomes compared with those with systemic lupus erythematosus. A better understanding of the mechanisms of neuropsychiatric systemic lupus erythematosus could potentially improve diagnosis and management. The goal of this study was to investigate the differences in the structural brain network of patients with neuropsychiatric systemic lupus erythematosus compared with patients with systemic lupus erythematosus by using brain connectivity analysis.MATERIALS AND METHODS: We recruited 20 subjects for each patient cohort and age-matched healthy controls. The topology and efficiency of the network and the characteristics of various brain hubs were investigated by using brain connectivity analysis of diffusion MR imaging data.RESULTS: There were more extensive reorganizations in the structural brain network of patients with neuropsychiatric systemic lupus erythematosus than in patients with systemic lupus erythematosus. For example, the network of the former had significantly decreased clustering coefficient and local efficiency. They also had significantly lower nodal efficiency in the superior temporal gyrus (P = .046) and middle temporal gyrus (P = .041).CONCLUSIONS: Our results hint at a plausible relationship between the neuropsychiatric symptoms and reorganization of the structural brain network of patients with systemic lupus erythematosus. Brain connectivity analysis may be a potential tool to subtype these patients.NPSLEneuropsychiatric systemic lupus erythematosusSLEsystemic lupus erythematosus